The Malaysia DREEM: perceptions of medical students about the learning environment in a medical school in Malaysia - Hisham S, Ibrahim Al-shaikhli; Redhwan A, Al-Naggar; Mahfoudh, Abdulghani (2014)
Background: Students’ perceptions of their learning environment, by defining its strengths and weaknesses, are important for continuous improvement of the educational environments and curriculum. Therefore, the aim of this study was to explore students’ perceptions of their learning environment, among medical students in Malaysia. Various aspects of the education environment were compared between year levels and sex. Methods: This cross-sectional study was conducted at the Management and Science University, Shah Alam, Malaysia in 2012. A total number of 438 medical students participated in this study, and the response rate was 87.6%. Data were analyzed using SPSS. Comparisons of the mean scores of Dundee Ready Education Environment Measure (DREEM) subscales were calculated. The t-test was used to determine statistically significant differences. Results: The majority of the study participants were female, Malay, and from year 3 (68.7%, 65.3%, and 55.7%; respectively). Analysis of each of the 50 items of the DREEM inventory showed that 47 items scored ranged between 2.00 and 3.00, and three items scored below 2.00. These were identified as problem areas in this medical school that are required to be critically addressed. The overall score showed that the medical students’ perceptions were positive. The students’ perception toward educational environment was positive for all five DREEM subscales. Conclusion: The study found that, in general, the perceptions of the participants about the learning environment were positive. Nevertheless, the study also found there is a need for curriculum improvement in this school and identified priority areas for such improvement.